The international - Tykwer, Tom, 1965-; Owen, Clive; Watts, Naomi, 1968-; Mueller-Stahl, Armin, 1930- (Culver City, Calif. : Sony Pictures Home Entertainment, 2009)
An Interpol agent works with a Manhattan assistant district attorney to work through layers of corruption and greed in a high-profile financial institution to expose an arms dealing ring.
Originally released as a motion picture in 2009.
Features: extended scene, making "The international," Shooting at the Guggenheim.
Clive Owen, Naomi Watts, Armin Mueller-Stahl, Ulrich Thomsen, Brian F. O'Byrne.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
In English or French with optional English, French, or Spanish subtitles.
Keywords: International Criminal Police Organization -- Drama; Criminal investigation -- Drama; Banks and banking -- Corrupt practices -- Drama; Video recordings for the hearing impaired; Fiction films; Thriller films; Feature films; Action and adventure films